2014
DOI: 10.1016/j.physletb.2014.05.083
|View full text |Cite
|
Sign up to set email alerts
|

New precision measurement of hyperfine splitting of positronium

Abstract: The ground state hyperfine splitting of positronium ∆ HFS is sensitive to high order corrections of quantum electrodynamics (QED) in bound state. The theoretical prediction and the averaged experimental value for ∆ HFS has a discrepancy of 15 ppm, which is equivalent to 3.9 standard deviations (s.d.). A new precision measurement which reduces the systematic uncertainty from the positronium thermalization effect was performed, in which the non-thermalization effect was measured to be as large as 10 ± 2 ppm in a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
69
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 35 publications
(22 reference statements)
5
69
0
Order By: Relevance
“…This would be achieved by observing the charge-transfer reaction (2), with the incident Ps in a Rydberg state. We have provided theoretical estimates for the cross section of this reaction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This would be achieved by observing the charge-transfer reaction (2), with the incident Ps in a Rydberg state. We have provided theoretical estimates for the cross section of this reaction.…”
Section: Discussionmentioning
confidence: 99%
“…(A.10), this latter result is valid for any Ps momentum K. Instead of having a plateau, the ionization cross section will then decrease with the Ps energy, following the decrease of the positron and electron cross sections σ ± . For Cu, supposing the incident Ps has an energy of 0.05 eV, for n = 15 the ionization cross section is estimated to be about 25πa 2 0 , while the charge-transfer cross section is approximately 125πa 2 0 , i.e., much greater. Depending on the Ps energy and the value of n, this may or may not be the case, but we have shown that there should be a 'window' of Ps energies and values of n where charge transfer is the dominant process.…”
Section: Appendix: Ps Ionization In Collisions With Atomsmentioning
confidence: 97%
See 2 more Smart Citations
“…Recently a new result with reduced systematic uncertainty from the positronium thermalization effect has been reported [5] ∆ν exp = 203.394 2(16) stat. (13) syst.…”
mentioning
confidence: 99%